Between Sacralization and Festivalization of Public Spaces: a Case Study of the Cavalcade of the Three Kings in Poland - Przybylska Lucyna (Bulletin of Geography. Socio-Economic Series)
The purpose of the paper is the identification and interpretation of the dynamically developing contemporary mass event called the Cavalcade of the Three Kings (Orszak Trzech Króli). It was organised for the first time in 2009 in Warsaw. On the 6th of January 2014, about 630, 000 inhabitants of 177 towns and villages, singing Christmas carols and wearing colourful crowns on their heads, publically celebrated the religious feast of Epiphany. In the author's opinion, the cavalcades can be perceived as a new phenomenon in public spaces placed between sacralization and festivalization because they have some components of religious events and festivals but they are neither. They seem to be a new hybrid event, with religious and festive elements.